2011
DOI: 10.1002/biot.201000405
|View full text |Cite
|
Sign up to set email alerts
|

Vitreoscilla hemoglobin expression in engineered Escherichia coli: Improved performance in high cell‐density batch cultivations

Abstract: High cell-density cultivations are the preferred system for biomolecules production by Escherichia coli. It has been previously demonstrated that a strain of E. coli with a modified substrate transport system is able to attain high cell densities in batch mode, due to the very low overflow metabolism displayed. The use of elevated amounts of glucose from the beginning of the cultivation, eliminates the existence of substrate gradients due to deficient mixing at large-scale. However, the large amounts of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…To better understand the effect of VHb on the engineered strain, the metabolic fluxes were estimated by flux balance analysis during the exponential growth of strains W3110 and VAL24. The simulations estimated values of μ close to the experimental values (data not shown) and the specific oxygen uptake rates estimated were in agreement with previously published values . The results are depicted in Fig.…”
Section: Resultssupporting
confidence: 91%
“…To better understand the effect of VHb on the engineered strain, the metabolic fluxes were estimated by flux balance analysis during the exponential growth of strains W3110 and VAL24. The simulations estimated values of μ close to the experimental values (data not shown) and the specific oxygen uptake rates estimated were in agreement with previously published values . The results are depicted in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The expression vector was previously designed in order to increase VHb synthesis under fully aerobic conditions. It was shown that, in this case, overflow metabolism was reduced and plasmid DNA yield was increased . VHb facilitates oxygen uptake from the media and delivers it to the cytochromes more efficiently, thus enhancing the electron transport chain activity.…”
Section: Resultsmentioning
confidence: 90%
“…To alleviate the oxygen‐limiting conditions, Vitreoscilla haemoglobin (VHb) has also been used to improve the production of metabolites in high cell‐density fermentation (Pablos et al . ). To the best of our knowledge, there are a few researches for investigating the effect of VHb gene on cell growth and lipid metabolism in oleaginous micro‐organisms (Liu et al .…”
Section: Introductionmentioning
confidence: 97%
“…Overexpression of VHb also increased alpha-amylase production and total protein secretion in Schwanniomyces occidentalis (Suthar and Chattoo 2006). To alleviate the oxygen-limiting conditions, Vitreoscilla haemoglobin (VHb) has also been used to improve the production of metabolites in high cell-density fermentation (Pablos et al 2011). To the best of our knowledge, there are a few researches for investigating the effect of VHb gene on cell growth and lipid metabolism in oleaginous micro-organisms (Liu et al 2017;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%